Louis Rosso and Hal Pepper at ASSED sales meeting - Laursen, Rene (1970)
Louis T. Rosso joined Beckman Instruments in 1959, initially working in product marketing in the biomedical instrumentation division. He assumed the role of chief operating officer and president of SmithKline Beckman in 1982. Rosso lead the company during a period of lackluster sales and hospitals’ efforts to control costs in response to revised Medicare regulations; he focused research and development spending on cost-efficient instruments and expanded international sales. Rosso served as president and chief executive officer after Beckman Instruments was spun off from Smith Kline in 1988 and retired after the 1998 acquisition of Coulter Corporation. Hal Pepper was a Beckman Instruments sales representative in the 1960s and was still with the company in an unknown capacity in the 1970s.
Keywords: Beckman Instruments, Inc.